Plan de Comunicación para el Fortalecimiento de la Organización y Comunicación de Médicos y Asociados Clinchimborazo Cía. Ltda. - Vinueza Montenegro, María José (2014)
The purpose of this study was to design a plan of internal and external communication for organizational strengthening and communication of Physicians and Associates Co. ClinChimborazo clinic. Ltda . Within the study began with a literature major focus on communication , identity, among others , as a basis for further development of research and proposed plan. Survey focused format officials occupying key positions in the administration area Clinic Doctors and Associate ClinChimborazo addition to the general population , in order to meet the diverse perspectives technique was used as primary data collection in order to develop a proper diagnosis of the current situation. Based on internal research, literature review and experience, a proposal was made , raising strategies that began with the socialization of the objectives and organizational philosophy , is also provided tools for internal communication as well as planned motivation staff , strengthen communication, has also sought to involve human talent with clinical and has set indicators for monitoring, evaluation and budget , supporting solidification processes brainstorming and finally be may strengthen the organization.